(untitled) (Research, Society and Development, 2018)
This paper discusses the educational action of the Municipal School Antônio Campos, aiming to understand the success of this institution, located in the neighborhood of Mãe Luiza, Eastern Region of Natal, in the State of Rio Grande do Norte. There are three indicators of success: first place in the National Reference in School Management Award, state stage; 6.5 in the IDEB and without student evasion or repetition. We research guided by Historical and Dialectical Materialism, from the school documents, by the application of the conversational free conversational interview and by the observation of the daily routine of the institution. We conclude that the school routine; the relationship of those responsible for the student with the institution; the evaluate-plan-evaluate triad, accomplished in the systematic accompaniment of the teaching and learning process of the student, are aspects that do not restrict the pedagogical are aspects that do not restrict the pedagogical to the knowledge constructed by the mediation of teaching in the room of knowledge that occur, specifically, in the process of student interaction in the in the classroom, nor is it an exclusive task of this professional. Other authors and actors in the school community also feel involved in the students’ school education process. This pedagogical thinking and acting therefore presents itself as a fertile field for a socially referenced school.